Changes during the sleep onset process on EEG activity and the components of attention - Borrani, Jorge; Chapa-Guerra, Alán; De-la-Garza, Vania; López, Iván; Isaias, Alba; Pimentel-Rodríguez, Luisa; García, Aída; Ramírez, Candelaria; Valdez, Pablo (Sleep Science, 2022)
The sleep onset process (SOP) happens every time a person falls asleep, regardless of the time of day or if they are doing an activity. Basic cognitive processes, such as attention, differ between wakefulness and sleep. The components of attention - tonic alertness, phasic alertness, selective, and sustained attention - are known to decrease during sleep, however they have not been analyzed during the sleep onset process. This study analyses the state of three of the four components of attention during the sleep onset process through electroencephalographic (EEG) activity and task performance in young people. Nine undergraduate students (18.54±1.24 years old) underwent a control session which was compared to the average of four sleep-inducing sessions. During all sessions, the EEG activity of the subjects was recorded to assess the effect of the SOP on electroencephalographic activity while they answered a continuous performance task (CPT) to assess the effect of the SOP on the components of attention. Comparisons of the EEG recordings of the control and the sleep inducing sessions demonstrated that there is lower activity in fast beta, as well as a higher theta and delta activity right before the sleep onset. There was a decrease in tonic alertness, phasic alertness, and selective attention. This study shows that there is an increase in EEG slow activity and a decrease in fast activity, as well as in attentional capacity during the SOP. This decrease can become a safety hazard since it could happen while performing daily activities.
Keywords: Attention; Sleep; Electroencephalography; Spectral Analysis; Sleep Onset; Continuous Performance Task